Teacher’s training from an interdisciplinary scope - Antonio García Correa,; Andrés Escarbajal Frutos; Tomás Izquierdo Rus (Revista Electrónica Interuniversitaria de Formación del Profesorado)
We are noticing that the society is involved in a deep social, cultural and economic change, which takes us a constant transformation on initial and permanent teacher’s training in all levels: child, primary, secondary and college education. Teachers have to be improving their objectives, contents and didactic methods permanently for the institutional and social improvement, innovation and development. First of all, we present a synthesis of different presentations that have contributed to the structure and large contents of the Congress. The lectures have dealt with thematic field related to social and cultural changes in the 21st century. Secondly, we have focused on a synthesis of the lectures presented by researchers, teachers and administrative assistants that have enriched us as a result of their contributions. This has allowed us to collect action lines, which in addition, help us to teach how to think, understand, be critical and build a more just, equal and democratic society. Finally, a number of accepted presentations have been taken into consideration in seventeen fields and their percentage of participation.